Audit technology and preferences for auditing standards - Kinney, William R. (Journal of Accounting and Economics, 1986)
This paper investigates factors associated with audit firm positions on Auditing Standards Board issues during the three-year period ending during 1984. The major finding is that firms with relatively structured audit technologies tend to favor proposed statements while firms with relatively unstructured technologies do not. Audit firm size is not associated with firm position. Also, Big 8 firms favoring proposed statements have lower staff-to-partner ratios and concentrate less in auditing. The staff-to-partner ratio is negatively associated with technology. The results' implications for auditing profession organization studies and auditing and financial reporting research are investigated.